Management of anterior dental caries and gingival pigmentation - Salsabila Nunki Widona; Arihta Putri; Nanik Zubaidah; Sri Kunarti; Adioro Soetojo; Ira Widjiastuti (Universitas Airlangga, 2026)
Background: Severe carious lesion and gingival pigmentation of anterior teeth can also make a patient's self-confidence level lower, so treatment in a complex aesthetics would be performed. Purpose: Elucidate the challenging aesthetic treatment and to restore shape, position, function, and aesthetics of patient’s anterior dental teeth. Case: A 20-year-old male patient came to Universitas Airlangga RSGMP with complaints of cavities in his front teeth and dark gums. Clinical examination revealed caries of teeth 12, 11, 21, 22, 23; rotation of tooth 22; and gingival pigmentation. Case Management: The patient's facial profile, teeth, and soft tissue were assessed using Digital Smile Design (DSD) before treatment. Furthermore, the treatment plans were as follows: 13, 21 = crown lengthening; maxillary and mandibular anterior = gingival abrasion; 11, 21, 22 = root canal treatment; 11, 21 = fiber post and porcelain fused to zirconia (PFZ) crown; 22 = customized metal post and PFZ crown; 23 = vital PFZ crown; and 12 = direct composite restoration. Discussion: Complex aesthetic treatment was performed comprehensively to restore shape, position, function, and aesthetics. DSD results showed gingival zeniths of teeth 13, 21 that did not match their contralateral teeth, necessitating crown lengthening. Restoration of tooth 22 with a customized metal post was chosen to correct the rotation of tooth 22. PFZ crowns were adjusted according to the DSD to be ideally positioned in the dental arch and to mimic natural teeth color.